FUNCTIONAL CHICKEN NUGGETS ENRICHED WITH DIETARY FIBRE FROM KODO MILLET-AN INDIAN NUTRI CEREAL - C. Vasanthi; V. Appa Rao; R. Narendra Babu; R. Karunakaran; S. Ezhilvelan; R. Ramani; M. Muthulakshmi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The optimization of Kodo millet (Paspalum scrobiculatum) as a healthy alternative to refined wheat flour (RWF) in chicken nuggets was investigated to assess dietary fibre enrichment. Replacement was performed at four levels: 5% (Tl), 6% (T2), 7% (T3), and 10% (T4), while control nuggets were prepared using RWF. Product quality, texture profile, sensory evaluation, and dietary fibre content were assessed. Emulsion stability and product yield remained statistically similar, with improved textural characteristics observed up to 7% replacement with Kodo millet. The product’s acceptance was highly significant (P<0.01) at 7% inclusion (7.61±0.32), with dietary fibre enrichment showing a 126.49% increase over the control. The findings concluded that 7% Kodo millet flour inclusion is the optimal level for dietary fibre enhancement in functional chicken meat nuggets.